5-Hydroxymethylfurfural and Alpha-Ketoglutaric Acid as an Ergogenic Aid During Intensified Soccer Training: A Placebo Controlled Randomized Study. (3rd March 2020) - Gatterer, Hannes; Böcksteiner, Thomas; Müller, Alexander; Simi, Helmut; Krasser, Christoph; Djukic, Radosav; Schroth, Rainer; Wallner, Dietmar
Abstract: Intensified training may lead to fatigue or even a state of overreaching with temporary reductions in performance. Any aid helping to prevent these consequences and to better tolerate such a training regime would be of great importance. 5-hydroxymethylfurfural (5-HMF) and α-ketoglutaric acid (α-KG) supplementation has been suggested to support favorable training outcomes but its effectiveness to facilitate adaptations during an intensified training period has never been investigated. During an in-season competition break (2 weeks), seventeen young outfield soccer players (age:14.7 ± 0.4 yr) performed a 9-day lasting shock microcyle including 5–7 repeated sprint exercise sessions in addition to the regular training (∼6 sessions/wk) and match (1–2 matches/wk) schedule. Before the training period a treadmill test to exhaustion, a YOYO intermittent recovery level 2 (YYIR2) and a repeated sprint ability (RSA) test were performed. The treadmill test was repeated 3 days after the shock microcycle whereas the YYIR2 and the RSA test on day 10 after the training. Magnitude based inference analysis showed likely positive effects of the 5-HMF/α-KG compared to the control group for changes in the maximal running velocity (+0.3 ± 0.7 vs. −0.3 ± 0.8 km/h) and running velocity at lactate turn-point 1 (+0.2 ± 0.4 vs. −0.2 ± 0.6) and lactate turn-point 2 (+0.4 ± 0.4 vs. −0.2 ± 0.6 km/h, for the 5-HMF/α-KG and placebo group, respectively). Training improved YYIR2 performance (+180 ± 67 vs. +200 ± 168m) and RSA (mean time: −0.1 ± 0.1 vs. −0.1 ± 0.1s, for the 5-HMF/α-KG and placebo group, respectively) in both groups and to the same extent. In conclusion, an in-season shock microcyle including repeated sprint training improves YYIR2 performance and RSA in youth soccer players. Supplementation with 5-HMF/α-KG did not modify training adaptations but led to likely positive exercise performance responses shortly after the intensified training regime.